A NEW METHOD OF TORQUE RIPPLE MEASUREMENT FOR MAGNETIC GEARS - Syam, Sudirman; Kurniati, Sri; Nursalim, Nursalim; Galla, Wellem F. (Jurnal Media Elektro, 2024)
Torque ripple analysis and calculation methods in an axial-type Magnetic Gear (MG) design with four rectangular NdFeB magnetic layers have been reviewed and discussed. Smooth and steadily transmitted torque is an essential characteristic of a magnetic gear. Reducing possible mechanical vibration, position inaccuracy, and acoustic noise is necessary. Therefore, this study aims to design a new engineering method appropriate for calculating the torque ripple of the MG transmission by testing its mechanical and electrical properties. Two simultaneous torque tests compare the MG brakes from zero to full load. In addition, the transmission torque of the axial MG is measured and calculated using technical methods. The results showed that differences in dynamic torque occurred in the MG at various air gap distances.